2014
DOI: 10.1037/a0031060
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and cultural reasons for delay in seeking help and nonadherence to treatment in Indonesian women with breast cancer: A qualitative study.

Abstract: The aim of this study was to explore reasons for delay in seeking medical help and nonadherence to treatment in Indonesian women with breast cancer. Method: Semistructured interviews were conducted by purposive sampling, using a consecutive sample of 50 breast cancer patients who were treated at the Outpatient Surgical Oncology Clinic of Hasan Sadikin Hospital in Bandung, Indonesia. Interviews were recorded, transcribed verbatim, and coded using qualitative software. Codes were merged into main themes that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 37 publications
6
85
1
5
Order By: Relevance
“…This is partly due to patients waiting on average almost 11 months between initial detection of symptoms and seeking organized cancer care. While this finding is consistent with previous studies in Ghana, it is elevated compared to both other LMICs and high income countries, and has a significant effect on patient prognosis and available treatment options [4, 10, 12, 15, 20]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is partly due to patients waiting on average almost 11 months between initial detection of symptoms and seeking organized cancer care. While this finding is consistent with previous studies in Ghana, it is elevated compared to both other LMICs and high income countries, and has a significant effect on patient prognosis and available treatment options [4, 10, 12, 15, 20]. …”
Section: Discussionsupporting
confidence: 92%
“…These factors –usually financial, geographical, and sociocultural- have also been implicated in motivating patients to seek alternative therapies [38, 12, 1417, 19–22]. Fear of mastectomy has been singled out as one of the major causes for delaying care and/or seeking alternative therapies; given that many women die shortly after mastectomy (due to late stage at presentation), there is a commonly perceived link between the procedure and death [4, 16, 21].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]7,10,11,[32][33][34][35][36][37] Interestingly, the categories of reasons that emerged from the present study mapped almost directly onto a general psychological model of responses to negative events-Crisis Decision Theory 30 -which has not previously been used as a framework for understanding medical care avoidance. Crisis Decision Theory posits that people respond to negative events first by appraising the severity of threat, next by identifying available response options, and lastly by evaluating available response options.…”
Section: Discussionmentioning
confidence: 98%
“…Many sociodemographic factors such as age, low socioeconomic status, area of residence, and appraisal of health services may be associated with some women delaying seeking medical consultation (Kannan & Veazie, 2015; Khakbazan, Taghipour, Latifnejad Roudsari, & Mohammadi, 2014; Robinson, Christensen, Ottesen, & Krasnik, 2011). Several factors associated with help-seeking delay include psychological factors such as: lack of awareness and knowledge of the disease, disease beliefs, treatment beliefs, and emotional distress (Iskandarsyah et al, 2014). Some data showed that a high level of initial emotional response to severe illness symptoms discovery was associated with a shorter delay in seeking medical help (Meechan, Collins, & Petrie, 2003).…”
Section: Beliefs About Pain Controlmentioning
confidence: 99%